The Effect of Enterprise Risk Management (ERM) Implementation on Operational Performance and Firm Value on Indonesian Agricultural Sector - Azar, Biko Kharunia; Ulpah, Maria (Dinasti Publisher, 2024)
The aim of this research is to analyze the effect of Enterprise Risk Management (ERM) implementation on Operational Performance and Firm Value in the Agricultural Industry sector during the 2016-2022 period. The information about ERM is taken from the annual reports, management reports and annual corporate governance reports disseminated over seven years (2016?2022). The data on firm performance have been obtained through financial report and the Eikon Refinitiv database of LSEG. Through a quantitative approach and panel data with linear regression, this study found that ERM contributes significantly to improved operational performance and firm value (measured through, Return on Assets and Tobin’s Q). These results show that the effective implementation of ERM can be an important strategy for improving the competitiveness and resilience of agricultural enterprises to the risks faced.